2005
DOI: 10.1007/s10531-004-0671-6
|View full text |Cite
|
Sign up to set email alerts
|

Structure, diversity, and regeneration of tropical dry deciduous forest of northern India

Abstract: This study examined the impact of disturbance on the pattern of diversity, forest structure and regeneration of tree species in the Vindhyan dry tropical forest of India. A total of 1500 quadrats distributed over five, 3-ha permanent plots in five sites, differing in degree of disturbance, were used to enumerate and measure the tree species. A total of 65 species with 136,983 individuals were enumerated in the total 15-ha area for stems ‡ 30 cm height. The number of species and number of stems ranged from 12 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
30
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 29 publications
7
30
1
3
Order By: Relevance
“…The low species richness obtained in the present study could be attributed to low and erratic rainfall pattern, anthropogenic perturbations and over grazing. However, the value obtained in the present study is closer to the values reported in tropical deciduous forests of Mudumalai (71/50 ha, Sukumar et al 1992) and Vindhyan dry tropical forests (65/15 ha, Sagar and Singh 2005). Quantitative inventories of tree species (≥10 cm dbh) across the tropics reveals a wide variation, ranging from 20 species ha -1 in flooded Varzea forest of Rio Xingu, Brazil (Campbell et al 1992) to 300 species ha -1 in terra firma, Yanamono, Peru (Gentry 1988).…”
Section: Resultssupporting
confidence: 84%
“…The low species richness obtained in the present study could be attributed to low and erratic rainfall pattern, anthropogenic perturbations and over grazing. However, the value obtained in the present study is closer to the values reported in tropical deciduous forests of Mudumalai (71/50 ha, Sukumar et al 1992) and Vindhyan dry tropical forests (65/15 ha, Sagar and Singh 2005). Quantitative inventories of tree species (≥10 cm dbh) across the tropics reveals a wide variation, ranging from 20 species ha -1 in flooded Varzea forest of Rio Xingu, Brazil (Campbell et al 1992) to 300 species ha -1 in terra firma, Yanamono, Peru (Gentry 1988).…”
Section: Resultssupporting
confidence: 84%
“…Estudios realizados sobre vegetación secundaria de bosques húmedos y selvas secas tropicales han documentado cambios en su estructura y composición florística (Lott et al, 1987;Guariguata et al, 1997;Gehring et al, 1999;Giraldo-Cañas, 2000, 2001Guariguata y Ostertag, 2001;Balvanera et al, 2002;Peña-Claros, 2003;Segura et al, 2003;Ruprecht, 2005;Sagar y Singh, 2005;Balvanera y Aguirre, 2006;Toledo y Salick, 2006;Durán et al, 2006;Lebrija-Trejos et al, 2008;Chazdon et al, 2010). Desafortunadamente, el conocimiento básico de la estructura y la diversidad de especies leñosas de la vegetación secundaria en la Península de Yucatán, han recibido poca atención (Rico-Gray y García-Franco, 1992;Mizrahi et al, 1997;González-Iturbe et al, 2002).…”
unclassified
“…Mora et al (2013) Un factor importante de por qué la comunidad evaluada presenta una diversidad alta puede ser el que la zona de estudio se ubica cercana a un área natural protegida, donde las actividades antropogénicas son mínimas, factor que influye en esta riqueza vegetal. De hecho, se ha demostrado que en áreas con disturbios existe una reducción en la diversidad de especies (e.g., Sánchez-Velásquez et al, 2002;Sagar y Singh, 2005;Verzino et al, 2005).…”
Section: Discussionunclassified